A FESTA DE SÃO JOÃO NA BAHIA - UM ROTEIRO TURÍSTICO: AMARGOSA, CRUZ DAS ALMAS E SENHOR DO BONFIM - Mascarenhas, Herika Silva (2010)
In the present study, does analyze the event of São João in the potential process for the local development. Beyond being a touristic activity of cultural character, it generates job and income for the cities contributing for the preservation of the regional and local culture exerting influences in other sectors of the local economy, divulges the image of the city in the e region in the country. Based in this principle, this dissertation has the objective of describe the June festivities as one event of cultural tourismo that has this attractive as local traditions in the cities of Amargosa, Cruz das Almas and Senhor do Bonfim. The specific objective is to verify the importance of São João for the local development, its positive and negative effect as well as its cultural traditions. The referencial is pautado in the theories of regional development and local, tourism, public policy and the São João festivities. The adopted methodology is the case study, on the basis of the collects of data acquired through questionnaires applied to the agents who act in the event: to be able publish place (organizers of the event), place community, place traders and tourist. From secondary data, geographic and socio and economic analysis of the region was also made where these cities are situated.